2014
DOI: 10.1371/journal.pone.0103420
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Differential Expression of Olfactory Genes in the Antennae of the Black Cutworm Moth Agrotis ipsilon

Abstract: Insects use their sensitive and selective olfactory system to detect outside chemical odorants, such as female sex pheromones and host plant volatiles. Several groups of olfactory proteins participate in the odorant detection process, including odorant binding proteins (OBPs), chemosensory proteins (CSPs), odorant receptors (ORs), ionotropic receptors (IRs) and sensory neuron membrane proteins (SNMPs). The identification and functional characterization of these olfactory proteins will enhance our knowledge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 90 publications
12
46
0
1
Order By: Relevance
“…The ORs with antennal-specific or dominant expression profiles may play crucial roles in olfactory chemoreception of wasps. Similar to the present study, it was reported that some ORs could be expressed in a variety of tissues apart the olfactory organs 58-60. Our previous work also suggests a divergent expression profile of ORs in M. mediator 40.…”
Section: Discussionsupporting
confidence: 92%
“…The ORs with antennal-specific or dominant expression profiles may play crucial roles in olfactory chemoreception of wasps. Similar to the present study, it was reported that some ORs could be expressed in a variety of tissues apart the olfactory organs 58-60. Our previous work also suggests a divergent expression profile of ORs in M. mediator 40.…”
Section: Discussionsupporting
confidence: 92%
“…Because insects use olfaction for a variety of behaviours, including mate attraction, mate searching, oviposition site selection and the detection of host plant volatiles [44, 45], we looked specifically for olfactory genes in the assembled transcriptome. We identified several transcripts of odorant binding proteins (OBPs), chemosensory proteins (CSPs), odorant receptors (ORs) and ionotropic receptors (IRs) (Additional file 1: Sheet 15).…”
Section: Resultsmentioning
confidence: 99%
“…3). Olfactory receptors play an important role in sex pheromone and odour detection, and their up-regulation in male suggests an essential role in sex pheromone detection in females [45]. Ionotropic receptors are ancient chemosensory receptors and respond to different odorants [46].…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that AlucOR genes exhibited diverse expression patterns, which could be briefly classified into five types: antennal highly expressed ORs, head highly expressed ORs, abdomen highly expressed ORs, wing highly expressed ORs, and broadly expressed ORs (Supplementary Table 2). It was also reported that some ORs could be expressed in a variety of tissues apart from the olfactory organs3739. Antennae are important sensory organs for insect, so the majority of AlucOR genes displayed high expressions in antennae, including female and male antennal highly expressed genes.…”
Section: Discussionmentioning
confidence: 99%